2014
DOI: 10.1530/eje-13-0761
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of pentraxin-3, an inflammatory protein involved in fertility, are reduced in women with polycystic ovary syndrome

Abstract: Objective: Pentraxin-3 (PTX3), like C-reactive protein (CRP), is an acute-phase protein that belongs to the pentraxin superfamily. Moreover, it is expressed in the cumulus oophorus and appears to be involved in female fertility. The aim of the present study was to assess whether PTX3 levels are altered in polycystic ovary syndrome (PCOS) women and whether they show any relationship with the main features of these subjects. Design: A cross-sectional study was conducted at the outpatient clinic of an academic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
3
17
1
Order By: Relevance
“…2c). Such observation of downregulated levels of PTX-3 in PCO model is also supported by recent reports in PCOS patients who have reduced levels of PTX-3 in serum [8]. In addition, TSG-6 and HABP1 were also up-regulated significantly during follicular maturation in SO (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2c). Such observation of downregulated levels of PTX-3 in PCO model is also supported by recent reports in PCOS patients who have reduced levels of PTX-3 in serum [8]. In addition, TSG-6 and HABP1 were also up-regulated significantly during follicular maturation in SO (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, normal follicles show HA (hyaluronan) and hyaluronan binding proteins [called as ''hyaladherins'' e.g., TSG-6 (TNF-a-stimulated gene/protein 6), PTX-3 (Pentraxin-3)] coordinated COC (cumulus-oocyte complex) expansion before successful ovulation [6,7], which is missing in PCO. Also recent studies highlight the reduction in serum PTX-3 levels in PCOS patients [8], supporting the above hypothesis. In addition, we have reported timedependent up-regulation of ovarian HABP1 (hyaluronan binding protein 1), another important hyaladherin, which starts from follicular expansion and COC maturation till ovulation (12 h post-hCG treatment) followed by repression during follicular luteinisation in PMSG-hCG primed rat.…”
Section: Introductionsupporting
confidence: 68%
“…Limited number of study has examined the relationship between PTX3 and PCOS. Tosi et al found that plasma PTX3 levels were reduced in women with PCOS [ 22 ]. Sari et al found PTX3 and CRP levels were similar in the PCOS compared to control group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, with regards to PCOS, PTX3 mRNA expression in PCOS patients correlates with fertilization processes [ 78 ] and could possibly be used as a biomarker for oocyte quality. However, consensus has not yet been reached; a study report that plasma PTX3 levels in women with PCOS is reduced [ 79 ], whereas yet another study shows PTX3 levels to be elevated in PCOS and positively correlated with insulin resistance [ 80 ]. As such, more research needs to be done before reaching a conclusion on the role of miR-224 in PCOS and whether altered PTX3 levels are a cause or consequence of the disease.…”
Section: Possible Role For Mirna In the Abnormal Follicular Develomentioning
confidence: 99%